Peningkatan Kesadaran Masyarakat untuk Gemar Makan Ikan: Pelatihan Pembuatan Es Dawet Belut Manis - Novia Anggraeni; Luqmanul Hakim; Fath Fadhilah. W (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2020)
The training on making Es Dawet Belut Manis (dawnis) was motivated by the abundance of produce from eel cultivation in Kandri Village, like the lack of consumption of fish in Indonesia. The aim of this program is to increase the use of eels as an effort to promote the movement to eat fish. This program focuses on Kandri Tourism Village people, there are three stages, namely exposure to the potential and nutritional content of eels, training in Es Dawnis making and marketing of Es Dawnis. From the three stages, it can be concluded that the Ice Dawnis making training program has been successfully implemented by observing the enthusiasm of the participants, product acceptance, and product marketing that could potentially introduce Es Dawnis as a typical drink for Kandri Tourism Village.